Pengaruh Dana Pihak Ketiga dan Perputaran Kas Terhadap Return On Asset (ROA) pada Bank Rakyat Indonesia, Tbk - Nur Amaliah; Aliah Pratiwi; Nafisah Nurulrahmatiah (Lembaga Pengembangan Kinerja Dosen, 2025)
This study investigates the impact of third-party funds and cash turnover on Return on Assets (ROA) at PT. Bank Rakyat Indonesia, Tbk. Specifically, it examines: (1) the effect of third-party funds on ROA, (2) the effect of cash turnover on ROA, and (3) the combined effect of third-party funds and cash turnover on ROA. Employing an associative research design with a quantitative approach, this study utilizes data on third-party funds, sales, cash, profit before tax, and total assets from 2013 to 2023. Data collection techniques include documentation and literature review. The analysis involves classical assumption tests (normality, multicollinearity, heteroscedasticity, and autocorrelation), multiple linear regression, and hypothesis testing (partial and simultaneous). The findings indicate that: (1) third-party funds significantly influence ROA, (2) cash turnover significantly affects ROA, and (3) both third-party funds and cash turnover collectively impact ROA at PT. Bank Rakyat Indonesia, Tbk.